2013
DOI: 10.1097/fbp.0b013e3283654216
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of NMDA glutamate and nicotinic acetylcholine receptor mechanisms in the discrimination of ethanol–nicotine mixtures

Abstract: Ethanol and nicotine are commonly co-abused drugs, and the incidence of co-dependence is greater than would be expected based on the summed probability of dependence on each drug alone. Previous findings from our laboratory and others suggest that interactive mechanisms at the level of discriminative stimulus (SD) effects may contribute to this co-abuse phenomenon. Specifically, ethanol overshadows the nicotine SD whereas nicotine potentiates the stimulus salience of ethanol when the two drugs are conditioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Such responsiveness promoted by nicotine may have contributed to the elevation in response rates in the NE-S D but not NE-S Δ group and also to the response rate differences between N and E during acquisition in Exp 2 and 3. By contrast, Ford et al (2012, 2013) reported that the discriminative stimulus effects of E exceeded N; however that study was conducted with mice and required much higher doses of nicotine (0.4–1.2 mg) and ethanol (1.5 g) to show the effects. Clearly, more parametric analyses involving dose-response manipulations will explicate the relative contribution of N and E to the NE compound in future investigations using extinction training, as the lack of such evaluations was an obvious limitation of the present set of studies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Such responsiveness promoted by nicotine may have contributed to the elevation in response rates in the NE-S D but not NE-S Δ group and also to the response rate differences between N and E during acquisition in Exp 2 and 3. By contrast, Ford et al (2012, 2013) reported that the discriminative stimulus effects of E exceeded N; however that study was conducted with mice and required much higher doses of nicotine (0.4–1.2 mg) and ethanol (1.5 g) to show the effects. Clearly, more parametric analyses involving dose-response manipulations will explicate the relative contribution of N and E to the NE compound in future investigations using extinction training, as the lack of such evaluations was an obvious limitation of the present set of studies.…”
Section: Discussionmentioning
confidence: 93%
“…Gauvin and Holloway concluded that stimulus salience (i.e., overshadowing) likely plays a role in discrimination of drug mixtures and that the perception of the NE compound, as a whole, does not likely differ from each of the elements (i.e., the NE compound is not a unique cue that differs from its elements). Most recently, Ford, Davis, McCracken, and Grant (2013), and also see Ford, McCracken, Davis, Ryabinin, and Grant (2012), conducted systematic replications in mice but found evidence that EtOH overshadowed nicotine; the NMDA glutamate receptor was found to play a role. To date, these are the only reported studies evaluating the stimulus effects of the NE compound.…”
mentioning
confidence: 99%
“…Given that individuals who use nicotine and alcohol regularly consume both together, the interoceptive effects are experienced together. It has previously been demonstrated by our lab and others that the combined nicotine and alcohol (N + A) interoceptive effects can be trained as a cue that predicts reward and represents a more complex cue than either the nicotine or alcohol components on their own . The present work seeks to build on these findings by exploring the role of two interconnected brain regions implicated in both associative learning (ie, drug discrimination) and drug‐seeking behavior: the medial prefrontal cortex (mPFC) and the nucleus accumbens core (AcbC).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, given the frequency with which nicotine and alcohol are used in combination, it is important to consider that individuals often experience the interoceptive effects of both substances together (i.e., a unique compound interoceptive cue). Indeed, preclinical work using operant drug discrimination models has shown that a compound nicotine+alcohol interoceptive cue can serve as a discriminative stimulus to modulate behavior (Ford et al 2013; Ford et al 2012; Gauvin and Holloway 1993; Troisi et al 2013). …”
Section: Introductionmentioning
confidence: 99%